ChemInform Abstract: Progress in the Synthesis and Transformations of Alkylidenecyclopropanes and Alkylidenecyclobutanes. Issue 41 (7th October 2014) - Brandi, Alberto; Cicchi, Stefano; Cordero, Franca M.; Goti, Andrea
Abstract Review: 747 refs.